1984
DOI: 10.1152/jappl.1984.56.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Influence of suspension hypokinesia on rat soleus muscle

Abstract: Hindlimb hypokinesia was induced in rats by the Morey method to characterize the response of the soleus muscle. Rats suspended for 1-4 wk exhibited continuous and significant declines in soleus mass, function, and contractile duration. Soleus speeding was in part explained by an alteration in fiber type. The normal incidence of 70-90% type I fibers in the soleus muscle was reduced after 4 wk of suspension to 50% or less in 9 of 11 rats. A significant decline in type I myosin isozyme content occurred without a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
2
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 0 publications
3
34
2
1
Order By: Relevance
“…They also reported that these changes might reflect a transformation of fast-twitch fibers to slow-twitch fibers. On the other hand, TEMPLETON et al (1984) and THOMASON et al (1987) reported an increase of fast-type myosin isozyme composition and fast-twitch fiber number, but no change in the total fiber number in various muscles following suspension hypokinesia. These results suggest that transformation from slow-twitch to fast-twitch type fiber occurred following suspension.…”
Section: Discussionmentioning
confidence: 93%
“…They also reported that these changes might reflect a transformation of fast-twitch fibers to slow-twitch fibers. On the other hand, TEMPLETON et al (1984) and THOMASON et al (1987) reported an increase of fast-type myosin isozyme composition and fast-twitch fiber number, but no change in the total fiber number in various muscles following suspension hypokinesia. These results suggest that transformation from slow-twitch to fast-twitch type fiber occurred following suspension.…”
Section: Discussionmentioning
confidence: 93%
“…[The Japanese Journal of Physiology 53: [77][78][79][80][81][82][83][84][85][86][87]2003] Numerous studies have shown that chronic hindlimb suspension reduces maximal tension, and induces a shortening in twitch development and relaxation of slow-twitch muscles. Furthermore, a shift in isometric twitch kinetic characteristics and potential dependence of activation and inactivation curves (calculated from K ϩ contracture experiments) toward those of fast-twitch muscles has also been reported [6][7][8][9]. Different approaches to reduce the effect of suspension have been tested, like chronic stimulation, removal of synergist muscle, and treatment with androgenic-anabolic steroids (AAS) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Gajdosik (2001) showed that passive stiffness was influenced by lengthening deformation of the connective tissues of the endomysium, perimysium, and epimysium (PEC) of the muscle belly with a large contribution of the perimysium due to its large amount in a muscle. After HH, a decrease in the concentration of myofibrillar proteins and a relative increase in the proportion of noncontractile tissue (Flynn and Max 1985;Herbert et al 1988;Templeton et al 1984) in the rat soleus muscles have been observed. More recently, Brown and Hasser (1996) have also described an increase in connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the passive tension of in situ rat soleus muscle increased after 7 and 14 days of whole body suspension (Gillette and Fell 1996). A relative increase in the proportion of noncontractile tissue particularly in the soleus and gastrocnemius muscles has also been described (Flynn and Max 1985;Herbert et al 1988;Templeton et al 1984). Therefore we suggest that the stretch transmission might be affected after an episode of HH and the electrophysiological afferent discharges of endings consequently modified.…”
Section: Introductionmentioning
confidence: 94%